Association of Hypertension with Body Mass Index in northern districts of Bangladesh (Bangladesh Journal of Medicine, 2024)
Background: Body Mass Index is one of the significant determinant associated with many disease process particularly hypertension. There is positive association between Body Mass Index (BMI) and blood pressure (BP). Lowering BMI with weight reduction significantly reduces blood pressure (BP). The main purpose of this study was to find out the association of BMI with hypertension. The aim of the study is to find out any association between BMI and hypertension in a particular area of Bangladesh.Methods: This is a retrospective study which involves review of written medical records for adults diagnosed with hypertension aged 18 years and above. This study was conducted at hypertension and research centre, Rangpur. A total of 14137 hypertensive patients were included in this study. Hypertension was defined by the Seventh Report of the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC 7). BMI was calculated by a person’s weight in kilograms divided by his height in meters squared.Results: Majority (42.1%) of hypertensive patients were within 41 to 50 years of age. Among 14137 participants 4.6% were underweight, 46.5% were healthy weight, 38.7% were overweight and 10.2& were obese. The mean values of systolic and diastolic blood pressure were144.9, 145.2, 148.3, 152.7 and 89.8, 90.4, 91.2, 92.8 respectively with increasing BMI.Conclusion: Increasing BMI increases the risk of HTN.Bangladesh J Medicine 2024; 35(1): 15-19